2017
DOI: 10.1021/acs.nanolett.7b00412
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Heterostructure as a Platform for Surface-Enhanced Raman Scattering

Abstract: Raman enhancement on a flat nonmetallic surface has attracted increasing attention, ever since the discovery of graphene enhanced Raman scattering. Recently, diverse two-dimensional layered materials have been applied as a flat surface for the Raman enhancement, attributed to different mechanisms. Looking beyond these isolated materials, atomic layers can be reassembled to design a heterostructure stacked layer by layer with an arbitrary chosen sequence, which allows the flow of charge carriers between neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 26 publications
4
127
1
Order By: Relevance
“…The CM effect is dictated by the interface electronic structures between the analyte and substrate and can be optimized by selecting a substrate with favorable band alignment with the highest‐occupied molecular orbital (HOMO) and the lowest‐unoccupied molecular orbital (LUMO) at the interface where the analyte (or probe molecule) bond to the substrate. Thus, tuning of the substrate electronic structure is important to an enhanced CM effect . This has prompted intensive research exploring graphene‐based SERS substrates considering the unique 2D atomically flat surface with delocalized π bonds, chemical inertness, biological compatibility, superior electronic and photonic properties, and the intrinsic Fermi energy at ≈4.5 eV that is compatible, as well as tunable, for CM enhancement with a large number of probe molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The CM effect is dictated by the interface electronic structures between the analyte and substrate and can be optimized by selecting a substrate with favorable band alignment with the highest‐occupied molecular orbital (HOMO) and the lowest‐unoccupied molecular orbital (LUMO) at the interface where the analyte (or probe molecule) bond to the substrate. Thus, tuning of the substrate electronic structure is important to an enhanced CM effect . This has prompted intensive research exploring graphene‐based SERS substrates considering the unique 2D atomically flat surface with delocalized π bonds, chemical inertness, biological compatibility, superior electronic and photonic properties, and the intrinsic Fermi energy at ≈4.5 eV that is compatible, as well as tunable, for CM enhancement with a large number of probe molecules .…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is similar to that of monolayer MoS 2 . [118] It is reported that electron-hole pairs can be separated at the interface between MX 2 and graphene under illumination due to the formation of a built-in electric field (as shown in Figure 13c,d).…”
Section: Optical Propertiesmentioning
confidence: 93%
“…By using ion beams, the properties of 2D materials could be modified in atomic scales . Defects could be introduced in on‐demand way, which brings out intermediate state in the band structures of specific 2D materials, extending the broadband applications in laser technology and sensing . For vertically stacked 2D materials, the out‐of‐plane charge transport can be enhanced through controllable formation of ion implanted point defects, leading to fast photoresponsivity for optimized devices .…”
Section: Optical Applications Of Ion Implantationmentioning
confidence: 99%
“…This result demonstrates that ion beam techniques also have promising prospects for modulating the performance of 2D materials‐based photodetectors. In addition, ion beam irradiation may also cause compressing effect along vertical dimension for few‐layer heterostructure materials, resulting in significant enhancement of layer‐to‐layer coupling …”
Section: Optical Applications Of Ion Implantationmentioning
confidence: 99%